ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA DOSEN STIPAS KEUSKUPAN AGUNG KUPANG - Taek, Emilia Dolorosa; Dau, Yoseph Lodowik Deki (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2020)
The focus of this research is to discover whether work motivation and lecturer’ competence influence lecturer’ performance at STIPAS Keuskupan Agung Kupang. The research method that used in this research is a quantitative method with an explanatory research approach to test the hypothesis. The data collection technique used a questionnaire which distributed to the research sample, and the data analysis technique uses descriptive data analysis and inferential data analysis. The results of the descriptive statistics analysis showed that the work motivation was catagorized as good, lecturers’ competence as good, and lecturers’ performance as good. The results of t-test showed that partially work motivation and lecturer’ competence had a positive and significant effect on the lecturer’ performance of STIPAS Keuskupan Agung Kupang. The results of F-test indicated that simultaneously the two independent variables: work motivation and, lecturers’ competence had a positive and significant effect on the lecturer’ competence. Therefore, these two variables are very necessary or very useful to improve the lecturer’ performance at STIPAS Keuskupan Agung Kupang, especially in the fields of education, research and community service.